DISPUTE RESOLUTION OF MUDHARABAH CONTRACT FINANCING THROUGH BASYARNAS - M Syafrie Ramadhan; Bagus Kusumo Hadi; Dino Gautman Raharjo; M. Fadhil Azzam Arfa; Muhammad Alvin Saputra (Universitas Muhammadiyah Surabaya, 2024)
Mudarabah financing disputes in Islamic banking are generally resolved using litigation or judicial channels. As stated in Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, there are also other channels in dispute resolution, namely arbitration and alternative dispute resolution such as; mediation. As contained in the financing contract in Islamic banking Law No. 21 of 2008 states that dispute resolution will be resolved through BASYARNAS if in the agreement clause a dispute occurs it will be determined through a Sharia arbitrator in this case BASYARNAS this is the authority for BASYARNAS. The settlement of mudharabah disputes in Islamic banking is said to be a default, not only judged by the losses obtained by the creditor (Bank) but can also come from the beginning of the loss. If the customer's negligence causes the default, then this can be the customer's responsibility as the owner of the capital, and he bears the loss. In principle, there is no compensation for mudharabah because it is Amanah. Still, if the loss comes from the negligence of the Islamic Bank, it will be borne by the Islamic Bank as long as the failure or loss is not caused by the owner of the capital (mudharib). if there is a dispute between the two parties to the mudharabah financing contract agreement, the settlement will be resolved through arbitration (BASYARNAS). This statement authorizes BASYARNAS to resolve disputes for the parties to the dispute according to the agreed agreement.